20問 足し算 分数足し算 数学・算数の教材公開ページ

20 

Loading....

Loading....

Loading....

Loading....

Loading....

全文

(1)

(1) 22 3 + 1

2

5 = (2) 3 1 6 + 2

1

3 = (3) 2 1 4 +

1 2 =

(4) 11 5 + 3

1

2 = (5) 2 1 2 + 1

3

4 = (6) 2 1 3 + 2

1 2 =

(7) 11 6 + 1

1

3 = (8) 3 1 3 + 2

1

6 = (9) 3 1 4 + 2

1 2 =

(10) 22 3 + 1

1

4 = (11) 3 2 3 + 3

1

2 = (12) 1 4 + 3

1 2 =

(13) 11 5 + 1

1

2 = (14) 1 6 + 5

1

3 = (15) 5 1 2 + 4

4 5 =

(16) 31 2 + 1

5

6 = (17) 1 2 3 + 1

5

6 = (18) 6 1 3 + 5

1 2 =

(2)

(1) 22 3 + 1

2

5 =

4

1

15

(2) 3

1 6 + 2

1

3 =

5

1

2

(3) 2

1 4 +

1 2 =

2

3

4

(4) 11 5 + 3

1

2 =

4

7

10

(5) 2

1 2 + 1

3

4 =

4

1

4

(6) 2

1 3 + 2

1 2 =

4

5

6

(7) 11 6 + 1

1

3 =

2

1

2

(8) 3

1 3 + 2

1

6 =

5

1

2

(9) 3

1 4 + 2

1 2 =

5

3

4

(10) 22 3 + 1

1

4 =

3

11

12

(11) 3

2 3 + 3

1

2 =

7

1

6

(12)

1 4 + 3

1 2 =

3

3

4

(13) 11 5 + 1

1

2 =

2

7

10

(14)

1 6 + 5

1

3 =

5

1

2

(15) 5

1 2 + 4

4

5 =

10

3

10

(16) 31 2 + 1

5

6 =

5

1

3

(17) 1

2 3 + 1

5

6 =

3

1

2

(18) 6

1 3 + 5

1

2 =

11

5

6

(19) 21 6 + 3

1

2 =

5

2

3

(20) 4

1 2 + 2

3

4 =

7

1

(3)

(1) 21 2 +

1

4 = (2) 3 1 2 + 2

3

4 = (3) 2 1 3 + 2

3 4 =

(4) 31 2 + 3

2

5 = (5) 3 1 2 + 4

4

5 = (6) 6 2 3 + 4

5 6 =

(7) 21 6 + 1

1

4 = (8) 1 5 6 + 3

1

3 = (9) 4 1 2 + 1

4 5 =

(10) 51 2 + 2

1

6 = (11) 4 1 3 + 3

5

6 = (12) 4 1 4 + 4

5 6 =

(13) 34 5 + 1

1

2 = (14) 1 1 6 + 2

1

3 = (15) 2 1 6 + 2

1 3 =

(16) 22 5 + 3

2

3 = (17) 1 5 + 1

3

4 = (18) 1 3 4 + 4

1 3 =

(4)

(1) 21 2 +

1 4 =

2

3

4

(2) 3

1 2 + 2

3

4 =

6

1

4

(3) 2

1 3 + 2

3 4 =

5

1

12

(4) 31 2 + 3

2

5 =

6

9

10

(5) 3

1 2 + 4

4

5 =

8

3

10

(6) 6

2 3 + 4

5

6 =

11

1

2

(7) 21 6 + 1

1

4 =

3

5

12

(8) 1

5 6 + 3

1

3 =

5

1

6

(9) 4

1 2 + 1

4 5 =

6

3

10

(10) 51 2 + 2

1

6 =

7

2

3

(11) 4

1 3 + 3

5

6 =

8

1

6

(12) 4

1 4 + 4

5 6 =

9

1

12

(13) 34 5 + 1

1

2 =

5

3

10

(14) 1

1 6 + 2

1

3 =

3

1

2

(15) 2

1 6 + 2

1 3 =

4

1

2

(16) 22 5 + 3

2

3 =

6

1

15

(17)

1 5 + 1

3

4 =

1

19

20

(18) 1

3 4 + 4

1 3 =

6

1

12

(19) 15 6 + 2

1

3 =

4

1

6

(20) 1

1 6 + 3

3

4 =

4

11

(5)

(1) 33 4 + 5

1

3 = (2) 3 4 5 + 5

1

4 = (3) 3 1 2 + 2

2 3 =

(4) 11 3 + 2

3

4 = (5) 2 1 3 + 1

5

6 = (6) 2 1 2 + 2

3 4 =

(7) 31 2 + 1

1

6 = (8) 1 1 6 + 1

2

3 = (9) 1 1 3 + 2

5 6 =

(10) 32 3 + 2

2

5 = (11) 2 5 6 + 3

2

3 = (12) 3 2 3 + 2

5 6 =

(13) 11 6 + 5

2

3 = (14) 4 1 2 + 2

2

3 = (15) 5 1 2 + 6

2 3 =

(16) 51 2 + 1

5

6 = (17) 4 3 4 + 2

1

2 = (18) 2 1 3 + 2

5 6 =

(6)

(1) 33 4 + 5

1

3 =

9

1

12

(2) 3

4 5 + 5

1

4 =

9

1

20

(3) 3

1 2 + 2

2 3 =

6

1

6

(4) 11 3 + 2

3

4 =

4

1

12

(5) 2

1 3 + 1

5

6 =

4

1

6

(6) 2

1 2 + 2

3 4 =

5

1

4

(7) 31 2 + 1

1

6 =

4

2

3

(8) 1

1 6 + 1

2

3 =

2

5

6

(9) 1

1 3 + 2

5 6 =

4

1

6

(10) 32 3 + 2

2

5 =

6

1

15

(11) 2

5 6 + 3

2

3 =

6

1

2

(12) 3

2 3 + 2

5 6 =

6

1

2

(13) 11 6 + 5

2

3 =

6

5

6

(14) 4

1 2 + 2

2

3 =

7

1

6

(15) 5

1 2 + 6

2

3 =

12

1

6

(16) 51 2 + 1

5

6 =

7

1

3

(17) 4

3 4 + 2

1

2 =

7

1

4

(18) 2

1 3 + 2

5 6 =

5

1

6

(19) 41 2 + 4

2

5 =

8

9

10

(20) 2

3 4 + 1

5

6 =

4

7

(7)

(1) 11 4 +

3

5 = (2)

5 6 + 3

1

2 = (3)

5 6 + 1

1 3 =

(4) 11 6 + 3

1

2 = (5) 1 5 6 + 6

1

2 = (6) 2 1 2 + 3

3 5 =

(7) 42 3 + 1

5

6 = (8) 2 1 6 + 5

3

4 = (9) 1 1 4 + 3

1 2 =

(10) 15 6 +

1

4 = (11) 1 1 6 + 1

1

4 = (12) 1 2 3 + 2

1 6 =

(13) 11 6 + 1

2

3 = (14) 3 3 4 + 4

1

2 = (15) 4 1 3 +

1 6 =

(16) 31 6 + 2

3

4 = (17) 1 1 2 + 1

1

5 = (18) 1 1 2 + 2

3 4 =

(8)

(1) 11 4 +

3 5 =

1

17

20

(2)

5 6 + 3

1

2 =

4

1

3

(3)

5 6 + 1

1 3 =

2

1

6

(4) 11 6 + 3

1

2 =

4

2

3

(5) 1

5 6 + 6

1

2 =

8

1

3

(6) 2

1 2 + 3

3 5 =

6

1

10

(7) 42 3 + 1

5

6 =

6

1

2

(8) 2

1 6 + 5

3

4 =

7

11

12

(9) 1

1 4 + 3

1 2 =

4

3

4

(10) 15 6 +

1 4 =

2

1

12

(11) 1

1 6 + 1

1

4 =

2

5

12

(12) 1

2 3 + 2

1 6 =

3

5

6

(13) 11 6 + 1

2

3 =

2

5

6

(14) 3

3 4 + 4

1

2 =

8

1

4

(15) 4

1 3 +

1 6 =

4

1

2

(16) 31 6 + 2

3

4 =

5

11

12

(17) 1

1 2 + 1

1

5 =

2

7

10

(18) 1

1 2 + 2

3 4 =

4

1

4

(19) 61 2 + 2

1

4 =

8

3

4

(20) 3

1 2 + 3

1

6 =

6

2

(9)

(1) 12 3 + 4

5

6 = (2) 4 1 4 + 5

1

2 = (3) 1 1 6 + 1

1 3 =

(4) 21 4 + 1

2

5 = (5) 1 1 3 + 2

1

2 = (6) 1 1 2 + 3

1 3 =

(7) 31 4 + 3

1

3 = (8) 3 5 6 + 2

2

3 = (9) 2 1 6 + 3

2 3 =

(10) 11 4 + 2

1

6 = (11) 1 1 2 + 1

1

4 = (12) 3 1 2 + 2

1 4 =

(13) 12 3 + 4

1

2 = (14) 1 1 2 + 2

3

4 = (15) 1 2 3 + 1

1 6 =

(16) 32 3 + 3

5

6 = (17) 4 3 4 + 2

1

2 = (18) 1 1 2 + 2

1 3 =

(10)

(1) 12 3 + 4

5

6 =

6

1

2

(2) 4

1 4 + 5

1

2 =

9

3

4

(3) 1

1 6 + 1

1 3 =

2

1

2

(4) 21 4 + 1

2

5 =

3

13

20

(5) 1

1 3 + 2

1

2 =

3

5

6

(6) 1

1 2 + 3

1 3 =

4

5

6

(7) 31 4 + 3

1

3 =

6

7

12

(8) 3

5 6 + 2

2

3 =

6

1

2

(9) 2

1 6 + 3

2 3 =

5

5

6

(10) 11 4 + 2

1

6 =

3

5

12

(11) 1

1 2 + 1

1

4 =

2

3

4

(12) 3

1 2 + 2

1 4 =

5

3

4

(13) 12 3 + 4

1

2 =

6

1

6

(14) 1

1 2 + 2

3

4 =

4

1

4

(15) 1

2 3 + 1

1 6 =

2

5

6

(16) 32 3 + 3

5

6 =

7

1

2

(17) 4

3 4 + 2

1

2 =

7

1

4

(18) 1

1 2 + 2

1 3 =

3

5

6

(19) 35 6 + 4

2

3 =

8

1

2

(20) 3

1 4 + 1

1

2 =

4

3

(11)

(1) 22 3 +

1

6 = (2) 3 2 3 + 1

5

6 = (3) 3 1 2 + 3

1 4 =

(4) 15 6 + 2

2

3 = (5) 5 1 2 + 1

1

3 = (6) 1 1 3 + 2

4 5 =

(7) 21 3 +

5

6 = (8) 5 1 3 + 4

5

6 = (9) 2 1 3 + 2

1 6 =

(10) 53 4 + 1

5

6 = (11) 1 2 3 + 1

1

6 = (12) 2 2 3 + 4

1 6 =

(13) 22 3 + 1

1

2 = (14) 2 3 + 1

1

6 = (15) 1 1 6 + 3

1 3 =

(16) 11 6 +

2

3 = (17) 2 1 3 + 5

5

6 = (18) 1 1 6 + 4

2 3 =

(12)

(1) 22 3 +

1 6 =

2

5

6

(2) 3

2 3 + 1

5

6 =

5

1

2

(3) 3

1 2 + 3

1 4 =

6

3

4

(4) 15 6 + 2

2

3 =

4

1

2

(5) 5

1 2 + 1

1

3 =

6

5

6

(6) 1

1 3 + 2

4 5 =

4

2

15

(7) 21 3 +

5 6 =

3

1

6

(8) 5

1 3 + 4

5

6 =

10

1

6

(9) 2

1 3 + 2

1 6 =

4

1

2

(10) 53 4 + 1

5

6 =

7

7

12

(11) 1

2 3 + 1

1

6 =

2

5

6

(12) 2

2 3 + 4

1 6 =

6

5

6

(13) 22 3 + 1

1

2 =

4

1

6

(14)

2 3 + 1

1

6 =

1

5

6

(15) 1

1 6 + 3

1 3 =

4

1

2

(16) 11 6 +

2 3 =

1

5

6

(17) 2

1 3 + 5

5

6 =

8

1

6

(18) 1

1 6 + 4

2 3 =

5

5

6

(19) 12 3 + 1

5

6 =

3

1

2

(20) 2

1 6 + 2

1

3 =

4

1

(13)

(1) 13 4 + 1

5

6 = (2) 1 1 3 + 2

2

5 = (3) 4 1 2 + 5

3 4 =

(4) 41 4 + 1

1

2 = (5) 4 1 2 + 2

1

4 = (6) 2 1 3 + 2

1 2 =

(7) 42 5 + 6

2

3 = (8) 4 1 4 +

1

2 = (9) 3 3 5 + 2

3 4 =

(10) 21 6 + 2

2

3 = (11) 2 2 3 + 1

3

5 = (12) 4 2 3 + 3

1 6 =

(13) 25 6 + 3

2

3 = (14) 2 1 3 + 1

5

6 = (15) 2 1 6 + 1

2 3 =

(16) 31 3 + 2

5

6 = (17) 3 5 6 + 3

1

3 = (18) 1 1 6 + 3

1 3 =

(14)

(1) 13 4 + 1

5

6 =

3

7

12

(2) 1

1 3 + 2

2

5 =

3

11

15

(3) 4

1 2 + 5

3

4 =

10

1

4

(4) 41 4 + 1

1

2 =

5

3

4

(5) 4

1 2 + 2

1

4 =

6

3

4

(6) 2

1 3 + 2

1 2 =

4

5

6

(7) 42 5 + 6

2

3 =

11

1

15

(8) 4

1 4 +

1

2 =

4

3

4

(9) 3

3 5 + 2

3 4 =

6

7

20

(10) 21 6 + 2

2

3 =

4

5

6

(11) 2

2 3 + 1

3

5 =

4

4

15

(12) 4

2 3 + 3

1 6 =

7

5

6

(13) 25 6 + 3

2

3 =

6

1

2

(14) 2

1 3 + 1

5

6 =

4

1

6

(15) 2

1 6 + 1

2 3 =

3

5

6

(16) 31 3 + 2

5

6 =

6

1

6

(17) 3

5 6 + 3

1

3 =

7

1

6

(18) 1

1 6 + 3

1 3 =

4

1

2

(19) 52 3 + 4

5

6 =

10

1

2

(20) 2

1 4 + 2

1

2 =

4

3

(15)

(1) 42 3 + 4

5

6 = (2) 1 1 6 + 3

2

3 = (3) 3 1 2 + 1

3 4 =

(4) 23 + 4 1

2 = (5) 1 1 2 + 2

1

4 = (6) 2 1 3 + 1

5 6 =

(7) 11 6 + 3

1

3 = (8) 5 1 3 + 3

1

2 = (9) 1 1 6 + 5

2 3 =

(10) 11 3 + 1

5

6 = (11) 1 3 4 + 2

4

5 = (12) 5 2 3 + 5

5 6 =

(13) 41 2 + 3

1

6 = (14) 3 4 5 + 5

1

2 = (15) 1 1 2 + 1

4 5 =

(16) 21 2 + 2

2

3 = (17) 1 1 6 + 1

1

2 = (18) 4 5 6 + 3

1 2 =

(16)

(1) 42 3 + 4

5

6 =

9

1

2

(2) 1

1 6 + 3

2

3 =

4

5

6

(3) 3

1 2 + 1

3 4 =

5

1

4

(4) 23 + 4 1 2 =

5

1

6

(5) 1

1 2 + 2

1

4 =

3

3

4

(6) 2

1 3 + 1

5 6 =

4

1

6

(7) 11 6 + 3

1

3 =

4

1

2

(8) 5

1 3 + 3

1

2 =

8

5

6

(9) 1

1 6 + 5

2 3 =

6

5

6

(10) 11 3 + 1

5

6 =

3

1

6

(11) 1

3 4 + 2

4

5 =

4

11

20

(12) 5

2 3 + 5

5

6 =

11

1

2

(13) 41 2 + 3

1

6 =

7

2

3

(14) 3

4 5 + 5

1

2 =

9

3

10

(15) 1

1 2 + 1

4 5 =

3

3

10

(16) 21 2 + 2

2

3 =

5

1

6

(17) 1

1 6 + 1

1

2 =

2

2

3

(18) 4

5 6 + 3

1 2 =

8

1

3

(19) 23 5 + 7

1

2 =

10

1

10

(20) 3

3 4 + 1

1

6 =

4

11

(17)

(1) 3 4 + 1

1

2 = (2) 4 1 3 + 1

1

6 = (3) 1 1 2 + 2

2 3 =

(4) 56 + 3 1

4 = (5) 3 5 6 + 1

2

3 = (6) 1 1 4 + 1

5 6 =

(7) 11 2 + 3

1

4 = (8) 4 1 3 + 3

1

4 = (9) 2 3 4 + 1

2 5 =

(10) 52 3 + 5

1

4 = (11) 2 5 + 2

1

4 = (12) 1 1 6 + 2

2 3 =

(13) 31 5 + 5

3

4 = (14) 1 5 6 + 4

1

2 = (15) 1 1 2 + 1

5 6 =

(16) 13 4 +

1

5 = (17) 3 3 4 + 3

4

5 = (18) 1 1 2 + 1

3 4 =

(18)

(1) 34 + 1 1 2 =

2

1

4

(2) 4

1 3 + 1

1

6 =

5

1

2

(3) 1

1 2 + 2

2 3 =

4

1

6

(4) 56 + 3 1 4 =

4

1

12

(5) 3

5 6 + 1

2

3 =

5

1

2

(6) 1

1 4 + 1

5 6 =

3

1

12

(7) 11 2 + 3

1

4 =

4

3

4

(8) 4

1 3 + 3

1

4 =

7

7

12

(9) 2

3 4 + 1

2 5 =

4

3

20

(10) 52 3 + 5

1

4 =

10

11

12

(11)

2 5 + 2

1

4 =

2

13

20

(12) 1

1 6 + 2

2 3 =

3

5

6

(13) 31 5 + 5

3

4 =

8

19

20

(14) 1

5 6 + 4

1

2 =

6

1

3

(15) 1

1 2 + 1

5 6 =

3

1

3

(16) 13 4 +

1 5 =

1

19

20

(17) 3

3 4 + 3

4

5 =

7

11

20

(18) 1

1 2 + 1

3 4 =

3

1

4

(19) 25 6 + 3

1

2 =

6

1

3

(20) 1

5 6 + 1

2

3 =

3

1

(19)

(1) 41 2 + 2

5

6 = (2) 1 1 2 +

5

6 = (3) 2 2 3 + 1

5 6 =

(4) 11 4 + 1

3

5 = (5) 4 2 3 + 3

5

6 = (6) 1 2 3 + 2

1 6 =

(7) 11 6 + 2

1

3 = (8) 2 3 4 + 1

1

6 = (9) 1 2 5 + 1

3 4 =

(10) 15 6 + 3

1

2 = (11) 1 1 5 + 1

1

4 = (12) 5 5 6 + 5

1 2 =

(13) 23 4 + 3

1

2 = (14) 3 4 + 2

1

2 = (15) 3 1 6 + 2

1 3 =

(16) 11 6 + 2

3

4 = (17) 3 1 4 + 2

5

6 = (18) 4 1 2 + 3

3 4 =

(20)

(1) 41 2 + 2

5

6 =

7

1

3

(2) 1

1 2 +

5

6 =

2

1

3

(3) 2

2 3 + 1

5 6 =

4

1

2

(4) 11 4 + 1

3

5 =

2

17

20

(5) 4

2 3 + 3

5

6 =

8

1

2

(6) 1

2 3 + 2

1 6 =

3

5

6

(7) 11 6 + 2

1

3 =

3

1

2

(8) 2

3 4 + 1

1

6 =

3

11

12

(9) 1

2 5 + 1

3 4 =

3

3

20

(10) 15 6 + 3

1

2 =

5

1

3

(11) 1

1 5 + 1

1

4 =

2

9

20

(12) 5

5 6 + 5

1

2 =

11

1

3

(13) 23 4 + 3

1

2 =

6

1

4

(14)

3 4 + 2

1

2 =

3

1

4

(15) 3

1 6 + 2

1 3 =

5

1

2

(16) 11 6 + 2

3

4 =

3

11

12

(17) 3

1 4 + 2

5

6 =

6

1

12

(18) 4

1 2 + 3

3 4 =

8

1

4

(19) 31 2 + 1

5

6 =

5

1

3

(20) 1

1 4 +

1

6 =

1

5

Updating...

参照

Updating...

関連した話題 :